2007
DOI: 10.1007/s10530-007-9183-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrating invasive mammal eradications and biodiversity offsets for fisheries bycatch: conservation opportunities and challenges for seabirds and sea turtles

Abstract: The removal of invasive mammals from islands is one of society's most powerful tools for preventing extinctions and restoring ecosystems. Given the demonstrable high conservation impact and return on investment of eradications, new networks are needed to fully leverage invasive mammal eradications programs for biodiversity conservation at-large. There have been over 800 invasive mammal eradications from islands, and emerging innovations in technology and techniques suggest that island area will soon no longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
1
40
0
1
Order By: Relevance
“…To date, there have been over 787 successful animal eradications from over 582 islands, including 284 rodent eradications (Howald et al 2007, Donlan and Wilcox 2008, Island Conservation 2010 Appendix 1 Population projection matrices built using demographic parameters on Buldir (1990Buldir ( -2010, Kasatochi (1996Kasatochi ( -2007, and Kiska (2001Kiska ( -2010 …”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been over 787 successful animal eradications from over 582 islands, including 284 rodent eradications (Howald et al 2007, Donlan and Wilcox 2008, Island Conservation 2010 Appendix 1 Population projection matrices built using demographic parameters on Buldir (1990Buldir ( -2010, Kasatochi (1996Kasatochi ( -2007, and Kiska (2001Kiska ( -2010 …”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that such coastalbased management to reduce predation to shorebird nests helps offset losses at sea as fisheries bycatch (Wilcox and Donlan, 2007). Moreover, and more recently, indications are that reducing predation on sea turtle nests also may mitigate losses at sea as fisheries bycatch for those species (Donlan and Wilcox, 2008). The logical extension of this would also imply general mitigation for calamities at sea such as oil spills.…”
Section: Discussionmentioning
confidence: 99%
“…sharks, turtles, seabirds). The conservation action suggested by Wilcox and Donlan (2007) and Donlan and Wilcox (2008) is to force industrial long-line fisheries to pay for compensating such mortality, using collected funds to restore habitat quality at breeding grounds, e.g. by eliminating invasive rats in seabird colonies.…”
Section: Survival Versus Breeding Habitatsmentioning
confidence: 99%